The underground chullpas of Yarcoq and the presence of puna wari shepherds in the Cordillera Negra, Ancash - Olvera, Juan Paredes (2021)
The present study shows the excavation results at the Yarcoq archaeological site, located on the eastern flank of the Cordillera Negra in the department of Ancash. The site is a cemetery composed of 18 funerary structures, where 14 are linked to the wari period and the other 4 to the recuay period. Two types of funerary architecture are evidenced, underground tombs and chullpas, each one with its particular characteristics and degree of sophistication, which were based on the resources that each group had access to build these monuments. These groups would have participated in a constant dynamic of exchange of products between the mountains and the coast, by which they would politically form a unit.